Estudio de impacto socio ambiental del proyecto: Construcción de trocha carrozable a nivel de afirmado, Nogalcucho, Granero, Kuelap, distrito de Tingo – Luya - Vega Tafur, Rolando Fredy (2014)
All human Activity cause changes in the atmosphere and is to hope that the projects of road improvement also cause them; reason why to be able to make the best decisions from handling on the projects the Study of Environmental lmpact has been proposed and recognized like an instrument that contributes to decide if they are justifiable or not environmentally. The present environmental study is elaborated in fulfillment to the effective legal norms in environmental matter, as well al? with the purpose of predicting, paying for anCI to raise preventive measures, corrective and/or of remediación before possible negative environmental impacts that they could cause during the implementation of the activities of the project and this form with giving an environmental viability. The Project of construction, has by purpose integration and the advantage of the existing tourist resources, facilitating the transport of people and load towards the main markets of Chachapoyas and the North coast of the country, reason why the Regional Government Amazon, has believed advisable the implementation and execution of this road project. The Section of the dirt road trail to construct, includes/understands the execution of diverse activities with aims to improve the quality of lite of the bordering populations, to lower the costs of transportwith the execution of the wagon section, to generate temporary jobs for the settlers of the zone, to integrate this route to the Tourist Runner Cajamarca, - Amazon-Saint Martín, in a length of 14+300 km, the project begins in section km 0+000, locality of Nogalcucho to an altitude of 1845 m.s.n.m. and it is developed in ascent happening through the sector of the Barn, finally to conclude in the locality of Kuelap located in km 14+300 to a 2675 altitude of m.s.n.m. Of the environmental analysis of the Project, one determines that the phase with greater negative effect on environment is the one of construction. According to the Matrix of Quantification of total impact (Method of Batelle), the factors of air and ground, in which it corresponds to contamination with dusts and noises (- 21) ·and modification of the ground (- 21) was the unique ones that values of negative impact of Smaller Significance caused and the factors that they had minor negative environmental incidence were the landscape, flora and fauna, catalogued like non Significant impacts. Also, the Matrix of Leopold, reveals that the negative potential impacts take place mainly during the stage of construction of the projected work, mainly bound to the activities of operation, earthwork of quarries, affirmed or ballast; where component the ground and air "more would be affected". On the other hand, according to the made evaluation, potential the environmental impacts of greater relevance are related to the stage of Operation of the projected road work, because the interchange will improve the conditions consequently to dinamizar the economy of the zone when allowing (people, products and information) and the socioeconomic development, with emphasis in the tourism, of the towns of the scope of the project. The matrix analysis concludes that the project is acceptable from the environmental point of view; inasmuch as the total values, as much of Magnitude (m) as of lmportance (i) throw positive results: 125 and 7207, respectively.